Calculus - Varberg, Dale E.; Purcell, Edwin J. (Edwin Joseph) 1901-; Rigdon, Steven E. 1955- (Pearson / Prentice Hall, 2007)
Intended for freshman/sophomore-level courses treating calculus of both one and several variables, this work helps students focus on, and understand vital concepts in calculus. It makes use of computing technology, graphics, and applications, and is useful for instructors.